Magnetostatic Interactions in Cylindrical Nanostructures with Non-Uniform Magnetization - Altbir-Drullinsky, D (2012)
Cylindrical magnetic nanostructures, like nanowires or nanotubes, should be used for the new generation of magnetic devices. Therefore, the investigation of inter-element interaction is an intense area of research. In this paper we investigated cylindrical nanostructures with non-uniform magnetization field. We focus on particles with a periodic magnetization function and using Fourier series we reduced the problem to a single integral expression. Analytical expressions for both, the self and the interaction magnetostatic energy, are given. These expressions are used to analyze multisegmented tubes, as a function of the number of segments and the distance between particles. © 2011 Elsevier B.V.